Ambient media, ambient media computation, and media technology beyond the current state - Lugmayr, Artur (2009)
McLuhan's statement, "the medium is the message" is all-present in discussions within the media community. However, how does ubiquitous and pervasive computation impact when the medium is 'inside' the natural environment of humans? How do location based services, context awareness, emotional responsive interfaces, touch and gesture based interfaces, haptic devices, biometrics, sensor data fusion, mobile embedded systems, distributed networks, and smart data mining change the way of how media are presented, distributed, and consumed? These technical enablers go far beyond existing well known computer screen concepts or simple keyboard and mouse interaction methods. Within the scope of the tutorial several aspects and viewpoints of ambient media are presented: media, technology, HCI, and business. The tutorial presents case-studies and latest research methods in the field of ambient media. Examples of existing services are coming from ambient assisting living, user experience design, sensor networks, distributed systems, and mobile location based services ambient media are explained in further detail. The tutorial intends to train participants in the principles of ambient media and its concepts, content creation techniques, and methods. The tutorial rounds up with a more visionary viewpoint towards media technology in the future: the use of biological metaphors in presenting media, shortly called biological media - 'biomedia'.